PROFILE OF LIPID FRACTION IN MENOPAUSEE WOMEN - ABBAS, MUTMAINNAH; THASLIFA; ALFYAN RAHIM (International Journal of Multidisciplinary Research and Studies, 2022)
Backgrounds: Menopause occurs in women around 50th years old. Reproductive phenomena occur due to hormonal changes during menopause, one of which is a decrease in the production of the hormone estrogen. The hormone estrogen is a steroid hormone and comes from cholesterol produced in the ovaries and plays a role in lipid metabolism which can increase triacylglycerol and High-Density Lipoprotein (HDL) levels, as well as reduce blood cholesterol and Low-Density Lipoprotein (LDL) levels. Objectives: To determine the profile of lipid fraction as a preventive measure for the incidence of dyslipidemia in menopausal women, which over time will develop into a risk factor for coronary heart disease. Methods: This study was an analytic observational study on a population of menopausal women aged 45-60 years in RT 02 / RW 06 of Antang district. Moh. Paleo 3/B with normal BMI was obtained through a purposive sampling technique from August-September 2020. Results: Results of research on 36 study subjects of menopausal women, the results of the lipid fraction profile of TG, LDL, HDL, and total cholesterol in menopausal women were the average levels of 121.5mg /dL, 166mg /dL, 48mg/ dL, and 218.5mg/dL. Conclusion: The profile of lipid fractions in menopausal women, namely levels of TG, LDL, and total cholesterol has increased and HDL levels have decreased. This suggests that menopausal women are at risk for dyslipidemia.